FINANCIAL PERFORMANCE ANALYSIS OF COMPANY VALUE ON REGISTERED BANKS ON THE INDONESIA STOCK EXCHANGE - Tiurmaulina Sinaga; Viola Syukrina E Janrosl (Institute of Computer Science (IOCS), 2022)
The purpose of this research is to study financial performance by using profitability ratios as proxied by Return On Assets, and solvency ratios proxied by Debt to Assets Ratios with firm value using Price to Book Value ratios. Companies in commercial banks on Indonesian Stock Exchange (IDX) commercial banks for the 2017-2021 period. The method used in this research is descriptive method using quantitative. The data used in this study is secondary data obtained from the company's financial performance. The population in this study were 43 banking companies. The technique used in this research is purposive sampling technique with a sample of 15 companies. While the data analysis used in this study is multiple linear regression, coefficients and determination using the SPSS 25 program calculation tool. The results of this study refer to the analysis of financial performance with Return On Assets having a negative/significant effect on firm value, and Debt to Assets Ratio does not have a significant effect on firm value. And simultaneously ROA and DAR have a significant effect on the dependent variable of Firm Value.